2014
DOI: 10.1155/2014/595186
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biochemical Characterization of a New Thrombin-Like Serine Protease fromBothrops pirajaiSnake Venom

Abstract: This paper presents a novel serine protease (SP) isolated from Bothrops pirajai, a venomous snake found solely in Brazil that belongs to the Viperidae family. The identified SP, named BpirSP-39, was isolated by three chromatographic steps (size exclusion, bioaffinity, and reverse phase chromatographies). The molecular mass of BpirSP-39 was estimated by SDS-PAGE and confirmed by mass spectrometry (39,408.32 Da). The protein was able to form fibrin networks, which was not observed in the presence of serine prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
1
17
0
3
Order By: Relevance
“…According to previous reports, many serine proteases have been identified from venomous animals [ 55 , 56 , 57 , 58 , 59 , 60 ]. A long time ago, some proteases were reported to be present in the venoms of both scolopendrid and cryptopid scolopendromorphs.…”
Section: Pharmacologically Important Proteins/peptides From Centipmentioning
confidence: 99%
“…According to previous reports, many serine proteases have been identified from venomous animals [ 55 , 56 , 57 , 58 , 59 , 60 ]. A long time ago, some proteases were reported to be present in the venoms of both scolopendrid and cryptopid scolopendromorphs.…”
Section: Pharmacologically Important Proteins/peptides From Centipmentioning
confidence: 99%
“…Correlated with the possible benefic effect of proteins present in the crude venom of Egyptian cobra encouraged us to develop an analytical method for separation as much protein as possible using reverse phase HPLC. Numerous previous publication reported separation of different peptides or proteins from crude snake venom [23][24][25][26][27][28][29]. Therefore, in this study we have reported the purification of Egyptian cobra venom as well as the antibacterial activity of crude venom.…”
Section: Discussionmentioning
confidence: 86%
“…Escherichia coli (ATCC 30040) and Staphylococcus aureus (ATCC 29213) used in this study were maintained in Tryptic Soy Broth (TSB) with glycerin media at -70°C. 24 hours before the study, the strains were revitalized on Columbia blood agar.…”
Section: Bacterial Stainsmentioning
confidence: 99%
“…halys , Ahv_TL‐I (PDB IDs: 4e7n.1.A), as the best templates, were refined with suitable stereochemical parameters and had highest structure quality . Templates with percent identities above 30% are sufficient to predict the three‐dimensional structure between template‐protein and target‐protein, and AhV_TL‐I has 62.93 – 96.20% identity ( Table ) with the sequence of agkihpin and some similar SVTLEs.…”
Section: Resultsmentioning
confidence: 99%